PENGARUH FINANCIAL RATIO, FIRM SIZE, DAN CASH FLOW OPERATING TERHADAP RETURN SHARE PERUSAHAAN F&B - yulia, lia; Sujana, Ketut (E-Jurnal Akuntansi; Vol 8 No 1 (2014), 2014)
The observation meaning to analises any signifikan connection between Financial Ratio, Firm Size and Cash Flow Operation for Return Share. The location of observation at F&B section in BEI. The total sample is 45 with Non Probability Sampling metode, especially Purposive Sampling, with double technic analisis regresi linear. The analisis test Current Ratio, Total Asset  Turnover, and Size Of Firm to influence positif and signifikan for return share. Debt to Equity Ratio to influence negatif and signifikan for Return Share, exactly Return On Equity and Cash Flow Operating not to influence as signifikan.
Keywords: financial ratios, firm size, operating cash flows and returns share